Magnetic resonance imaging based kidney volume assessment for risk stratification in pediatric autosomal dominant polycystic kidney disease - Yilmaz, Kubra; Saygili, Seha; Canpolat, Nur; Akgun-Dogan, Ozlem; Yuruk Yildirim, Zeynep Nagehan; Cicek-Oksuz, Rumeysa Yasemin; Oner, Huseyin Adil; Aksu, Bagdagul; Akyel, Nazli Gulsum; Oguzhan-Hamis, Ozge; Dursun, Hasan; Yavuz, Sevgi; et al. (Frontiers in Pediatrics, 2024)
In the pediatric context, most children with autosomal dominant polycystic kidney disease (ADPKD) maintain a normal glomerular filtration rate (GFR) despite underlying structural kidney damage, highlighting the critical need for early intervention and predictive markers. Due to the inverse relationship between kidney volume and kidney function, risk assessments have been presented on the basis of kidney volume. The aim of this study was to use magnetic resonance imaging (MRI)-based kidney volume assessment for risk stratification in pediatric ADPKD and to investigate clinical and genetic differences among risk groups.This multicenter, cross-sectional, and case-control study included 75 genetically confirmed pediatric ADPKD patients (5-18 years) and 27 controls. Kidney function was assessed by eGFR calculated from serum creatinine and cystatin C using the CKiD-U25 equation. Blood pressure was assessed by both office and 24-hour ambulatory measurements. Kidney volume was calculated from MRI using the stereological method. Total kidney volume was adjusted for the height (htTKV). Patients were stratified from A to E classes according to the Leuven Imaging Classification (LIC) using MRI-derived htTKV.Median (Q1-Q3) age of the patients was 6.0 (2.0-10.0) years, 56% were male. There were no differences in sex, age, height-SDS, or GFR between the patient and control groups. Of the patients, 89% had PKD1 and 11% had PKD2 mutations. Non-missense mutations were 73% in PKD1 and 75% in PKD2. Twenty patients (27%) had hypertension based on ABPM. Median htTKV of the patients was significantly higher than controls (141 vs 117 mL/m, p=0.0003). LIC stratification revealed Classes A (38.7%), B (28%), C (24%), and D+E (9.3%). All children in class D+E and 94% in class C had PKD1 variants. Class D+E patients had significantly higher blood pressure values and hypertension compared to other classes (p> 0.05 for all).This study distinguishes itself by using MRI-based measurements of kidney volume to stratify pediatric ADPKD patients into specific risk groups. It is important to note that PKD1 mutation and elevated blood pressure were higher in the high-risk groups stratified by age and kidney volume. Our results need to be confirmed in further studies.